Electrophysiological characterization of spinal neuronal response properties in anaesthetized rats after ligation of spinal nerves L5-L6 - Chapman, Victoria (Blackwell Science Inc, 1998)
1. Despite a number of models of nerve injury, few studies have examined how peripheral nerve injury influences spinal somatosensory processing. 2. Ligation of two (L5-L6) of the three spinal nerves that form the sciatic nerve produces a partial denervation of the hindlimb. Following ligation, rats exhibited withdrawal responses to normally innocuous punctate mechanical and cooling stimuli (acetone) applied to the lesioned hindpaw. Such mechanical and cooling allodynia was not observed in sham-operated rats. 3. A significantly greater proportion of spinal neurones of ligated rats exhibited spontaneous activity at post-operative (PO) days 7–10 (P = 0.03) and 14–17 (P = 0.0001), compared with sham controls. The frequency of the spontaneous activity was significantly higher than that of the sham controls (P = 0.03 and P = 0.02 for days 7–10 and days 14–17, respectively). 4. At the earlier PO period, significantly (P = 0.02) more neurones of spinal nerve-ligated (SNL) rats responded to brush compared with the sham controls; at the later PO period the proportion of neurones of SNL rats responsive to prod was significantly (P = 0.007) reduced compared with the sham controls. The magnitude of the evoked neuronal response of SNL rats at PO days 7–10 was comparable to that of the sham controls. The magnitudes of brush- and prod-evoked neuronal responses of SNL rats were significantly smaller (P = 0.05 and P = 0.002, respectively) than the sham controls at PO days 14–17. In addition, neuronal responses of SNL rats to mechanical punctate stimuli and the C fibre-evoked neuronal responses were significantly reduced at the later PO period, compared with sham controls. Aβ-fibre-induced wind-up was not observed under any conditions. 5. These complex changes in neuronal responses are both time and modality dependent. The plasticity of some of the neuronal and behavioural responses following nerve injury was difficult to reconcile. We suggest that an interplay between pathological peripheral and central mechanisms may account for some of the changes that could contribute to allodynia and hyperalgesia.